Vermont State Papers, Being a Collection of Records and Documents, Connected with the Assumption and Establishment of Government by the People of Vermont 305 (1823) - (:unkn) unknown (My University, 1779)
Provided that "all male persons, from sixteen years of age to fifty, shall bear arms." The firearm could be "a well fixed firelock, the barrel not less than three feet and a half long, or other good fire-arms." The edged arm was to be "a good sword, cutlass, tomahawk or bayonet." For cleaning, a soldier or "other householder" needed "a worm, and priming-wire, fit for each gun." Suitable ammunition storage for a solider could be with "a cartouch box, or powder-horn and bullet-pouch." Adequate supplies were at least a pound of gun powder, four pounds of bullets, "and six good flints."
Keywords: REQUIRED POSSESSION